Advantages of Computer Intelligent Simulation on Taijiquan Teaching - Meng Xue (Institute of Advanced Engineering and Science, 2013)
This paper firstly analyzes the advantages of computer intelligent simulation teaching. On this basis it combines with the characteristics of Taijiquan teaching. Based on the analysis of mathematic model, it applies the advantages of computer intelligent simulation in Taijiquan Teaching to further deepen and construct optimized Taijiquan teaching model based on computer intelligent simulation. It enhances the systematicness and practicality of teaching system in the field of Taijiquan teaching, which plays a great promoting role on deepening the research of Taijiquan teaching to improve learners′ technical level. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3293